Ventriculocisternostomia de Torkildsen no tratamento do hidrocefalo não comunicante: resultados em 67 casos - José A. Gonçalves da Silva; Kurt Schuermann; Hermann Dietz (Arquivos de Neuro-Psiquiatria)
Sixty-seven cases of non-communicating hydrocephalus treated according to the Torkildsen's procedure are reported. The spinal fluid blockage was caused in 55 cases by supratentorial and in 10 cases by infratentorial tumors; in the remaining cases the spinal fluid interruption was due to non-tumoral causes. Ventriculography was the most important examination performed as far as the local diagnosis was concerned. 15 patients in this series disclosed lethal complications with signs of brain stem lesions. Patient survival was 3.9 years with variation ranging from 1 to 9 years. The following conclusions were drawn: 1) Ventriculocisternostomy is a valious method for the treatment of non-communicating hidrocephalus for it allows a more physiological drainage of the spinal fluid besides favouring the exploration of the posterior fossa in cases of doudtful pre-operative diagnosis. This procedure is of low cost and involves a relatively simple tecnique as compared with other procedures which demand the use of special valves. 2) According to the review of the pertinent literature the best results have been accomplished in cases where there is a non-tumoral aqueduct stenosis as well as in inoperable tumors of the third ventricle. 3) Bilateral drainage is mandatory in cases of bilateral obstruction of Monro's foramina. It has also been indicated in all cases as a precaution due to the possibility of occlusion of one catheter. 4) Ventriculocisternostomy should also be indicated as a prophylactic treatment of non-communicating hydrocephalus in cases of inoperable tumors of the sela or the basal ganglia with compression of the third ventricle but without completly blockage of the ventricle system. 5) Ventriculocisternostomy should be indicated with some reserve in cases of infratentorial tumors as well as in great supratentorial space-occupying lesions. It is however contra-indicated in cases of large tumors and in the inflammatory process involving the posterior fossa. 6) In the present series the obstruction of the draining-system was very uncommon being observed in only three patients. 7) No cases of spinal fluid fistula or meningitis were observed in the present study.